The Role of Relationship Management and Word of Mouth in Building Trust and Revisit Intention at Hotels in Batam - Stanley Asyer Francisco Tay; Renza Fahlevi; Fitriana Aidnilla Sinambela (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of RM and WOM on revisit intention with trust as a mediating variable among customers of 4-star hotels in Batam City. A quantitative approach was used with the Structural Equation Modeling Partial Least Square (SEM-PLS) method. Data were obtained through a survey of 120 respondents who had stayed at 4-star hotels, using purposive sampling techniques. The results show that RM and WOM have a positive and significant effect on trust. However, trust does not have a significant effect on revisit intention. RM also does not have a direct effect on revisit intention. Meanwhile, WOM has a positive and significant effect on revisit intention. These findings indicate that promotion through customer-to-customer communication is more effective in encouraging revisit intention than relationship-based marketing alone. This study provides practical implications for hotel managers to strengthen WOM strategies, as well as opening up opportunities for further research by considering additional variables such as customer satisfaction and stay experience.